Cardiovascular and Systemic Microvascular Effects of Anti-Vascular Endothelial Growth Factor Therapy for Cancer - Belcik, J. Todd (2012)
OBJECTIVES: This study sought to evaluate the contribution of microvascular functional rarefaction and changes in vascular mechanical properties to the development of hypertension and secondary ventricular remodeling that occurs with anti-vascular endothelial growth factor (VEGF) therapy. BACKGROUND: Hypertension is a common side effect of VEGF inhibitors used in cancer medicine. METHODS: Mice were treated for 5 weeks with an anti-murine VEGF-A monoclonal antibody, antibody plus ramipril, or sham treatment. Microvascular blood flow (MBF) and blood volume (MBV) were quantified by contrast-enhanced ultrasound in skeletal muscle, left ventricle (LV), and kidney. Echocardiography and invasive hemodynamics were used to assess ventricular function, dimensions and vascular mechanical properties. RESULTS: Ambulatory blood pressure increased gradually over the first 3 weeks of anti-VEGF therapy. Compared with controls, anti-VEGF–treated mice had similar aortic elastic modulus and histological appearance, but a marked increase in arterial elastance, indicating increased afterload, and elevated plasma angiotensin II. Increased afterload in treated mice led to concentric LV remodeling and reduced stroke volume without impaired LV contractility determined by LV peak change in pressure over time (dp/dt) and the end-systolic dimension–pressure relation. Anti-VEGF therapy did not alter MBF or MBV in skeletal muscle, myocardium, or kidney; but did produce cortical mesangial glomerulosclerosis. Ramipril therapy almost entirely prevented the adverse hemodynamic effects, increased afterload, and LV remodeling in anti-VEGF–treated mice. CONCLUSIONS: Neither reduced functional microvascular density nor major alterations in arterial mechanical properties are primary causes of hypertension during anti-VEGF therapy. Inhibition of VEGF leads to an afterload mismatch state, increased angiotensin II, and LV remodeling, which are all ameliorated by angiotensin-converting enzyme inhibition.